The origins of early Christian literature: contextualizing the New Testament within Greco-Roman literary culture - Walsh, Robyn Faith (University of Cambridge ESOL Examinations, 2021)
The Synoptic gospels were written by elites educated in Greco-Roman literature, not exclusively by and for early Christian communities.